Penerapan Data Mining Pengarsipan Pada Kantor Urusan Agama Medan Deli - Utari, Windi (U-NET Jurnal Teknik Informatika, 2023)
The Office of Religious Affairs (KUA) is a government agency that carries out the duties and functions of the Ministry of Religion in the religious field, whose main function is to provide services to the community in the surrounding environment in terms of religious guidance and services. In the service process, KUA as a government agency documents all activities it does, including the process of correspondence. The KUA Medan Deli, which is the object of the case study in this study, uses a conventional mail archive management system, so that the efficiency and effectiveness in carrying out its operations is low. the archive management information system at KUA Medan Deli is a solution that can optimize the work performance of the filing process. Developed with the fish bone method for its manufacture. the Medan Deli KUA information system is able to minimize the allocation of storage places that previously used cupboards, speeding up the data search process because it has been integrated into the system, where previously the data was only stored in physical form, so that various kinds of modern system advantages are found in the Medan Deli KUA information system., and become a disease representative directly in the network